Analisis Kondisi Lingkungan Sebagai Faktor Risiko Infeksi Kecacingan pada Siswa Madrasah Ibtida’iyah di Kecamatan Banjarsari, Kabupaten Lebak - Trasia, Reqgi First; Sasmita, Guruh Nata; Irawati, Nur Bebi Ulfah (Jurnal EnviScience (Environment Science), 2025)
The level of helminth infection in Banten Province reached 60.7%, with the highest case being in Lebak District, which is around 63.4%. This study is an analytic observational study using a cross-sectional study design and the sampling technique used is consecutive sampling. In this study, it was found that the proportion of Madrasah Ibtida'iyah students in Banjarsari Subdistrict, Lebak Regency who were at high risk of Soil Transmitted Helminths (STH) infection was 50.5%, the proportion of Madrasah Ibtida'iyah students in Banjarsari Subdistrict, Lebak Regency with poor nail hygiene was 14.7%, the habit of wearing footwear was 13.7%, and the socioeconomic status of the lower middle class was 81.1%. The proportion of Madrasah Ibtida'iyah students in Banjarsari Subdistrict, Lebak Regency who are at high risk of Soil Transmitted Helminths (STH) infection is 50.5%, the proportion of Madrasah Ibtida'iyah students in Banjarsari Subdistrict, Lebak Regency with poor personal hygiene between nail hygiene and the habit of wearing footwear, namely, poor nail hygiene is 14.7%, the habit of wearing footwear is 13.7%, the proportion of Madrasah Ibtida'iyah students in Banjarsari Subdistrict, Lebak Regency with lower-middle socioeconomic status as much as 81.1%, and a significant relationship was found between the habit of wearing footwear with a high risk of STH infection (p-value 0.000), but no significant relationship was found between nail hygiene with the risk of infection in Madrasah Ibtida'iyah students in Banjarsari District, Lebak Regency (p-value 0.090), and there was a significant relationship between the socioeconomic status of students with a high risk of STH infection (pvalue 0.000).